Perceived environmental concern, knowledge, and intention to visit green hotels: Do perceived consumption values matter? - Odugbesan Jamiu Adetola; Sahar Aghazadeh; Maryam Abdullahi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
Though, the call for environmental protection is on the increase, the ability of the hotel consumers to pay for green product is still a challenge for tourism industry. This study sought to expand existing understanding of consumer's environmental concern and knowledge in relation to consumers' green hotels visiting intention by testing the extended social exchange theory. Specifically, perceived environmental knowledge and concern were incorporated into the social exchange theory to understand comprehensively consumer's perceived consumption values with respect to their intention to visit green hotels. The data from 401 hotel guests in Nigerian hotels was analyzed using partial least square - structural equation modeling (PLS-SEM) by using WarpPLS 7.0 software. Results show that the theoretical framework proposed in the study has a significant capability to determine intention and identified significant impact of perceived environmental knowledge, concern and consumption values in generating intention to visit green hotels, as well as the significant mediating effect of perceived consumption value in the model. The finding from this study provides additional perspective into consumers' process of decision-making, with an implication for hotel managers in the development and execution of hotel operations that would account for eco-friendly purchase behavior among hotel guests in Nigeria.
Keywords: 330; eco-friendly hotels; social exchange theory; perceived consumption values; Nigeria